Why we should care about asylum seeking Latina pregnant migrants - Cuervo, Maria; Venta, Amanda (Frontiers in Child and Adolescent Psychiatry, 2025)
Latina immigrants seeking asylum in the U.S. report high levels of trauma exposure and posttraumatic distress. Our clinical and research experiences highlight the prevalence of these health disparities for pregnant migrants, with serious consequences for them as well as for the developmental trajectory of their children. This minireview focuses on asylum seeking Latina pregnant migrants, and the implications current polices, and circumstances have on their health and wellbeing as well as their children's health and well-being.